Manipulating interphase reactions for mechanically robust, flame-retardant and sustainable polylactide biocomposites. (1st June 2020) - Xu, Xiaodong; Dai, Jinfeng; Ma, Zhewen; Liu, Lina; Zhang, Xinghong; Liu, Hongzhi; Tang, Long-Cheng; Huang, Guobo; Wang, Hao; Song, Pingan
Abstract: The creation of high-performance polylactic acid (PLA) materials combining excellent mechanical robustness and flame-retardant performances are essential to meet demanding performances requirements for their practical applications in industry. Despite encouraging advances, current strategies by introducing toughening agents and flame retardants usually show compromised mechanical strength/ductility because of the irrational interphase reaction design of multi-component polymer blends. To date it remains challenging to robust and flame-retardant PLA via controlling interphase reactions. We, herein, report the rational design of mechanically robust and flame-retardant PLA by in situ manipulating interphase reactions between PLA, epoxidized soybean oil (ESO), a biobased and inexpensive toughening agent, and ammonia polyphosphate (APP), an effective eco-friendly flame retardant. We show that in addition to a high tensile strength of 42.0 MPa, as-designed PLA/ESO/APP ternary blend exhibits a high extensibility of 165% and a fracture toughness as high as 46 MJ/m 3, which are respectively 21 and 14 folds of that of the bulk PLA. Meanwhile, a desired V-0 rating and a high limited oxygen index of 30.2% are achieved. Such outstanding performance portfolios are enabled by the rational manipulation of interphase reactions, leading to the in situ formation of favorable phase structures. This work offers an innovative methodology for facilely and massively creating high-performance multi-component polymer blends by tailoring interphase reactions, and contributes to expanding the extensive applications of PLA. Graphical abstract: Image 1 Highlights: Advanced PLA/ESO/APP ternary blends have been rationally designed via manipulating interphase reactions. As-designed PLA/ESO/APP blend exhibits a large extensibility of 165% and a fracture toughness as high as 46 MJ/m 3 . The PLA/ESO/APP ternary blend retains a high tensile strength of 42.0 MPa. The PLA/ESO/APP blend can pass a V-0 rating in addition to showing a high LOI of 30.2%.